Pre-complexation of talin and vinculin without tension is required for efficient nascent adhesion maturation - Han, Sangyoon J; Azarova, Evgenia V; Whitewood, Austin J; Bachir, Alexia; Guttierrez, Edgar; Groisman, Alex; Horwitz, Alan R; Goult, Benjamin T; Dean, Kevin M; Danuser, Gaudenz (eLife, 2021)
Talin and vinculin are mechanosensitive proteins that are recruited early to integrin-based nascent adhesions (NAs). In two epithelial cell systems with well-delineated NA formation, we find these molecules concurrently recruited to the subclass of NAs maturing to focal adhesions. After the initial recruitment under minimal load, vinculin accumulates in maturing NAs at a ~ fivefold higher rate than in non-maturing NAs, and is accompanied by a faster traction force increase. We identify the R8 domain in talin, which exposes a vinculin-binding-site (VBS) in the absence of load, as required for NA maturation. Disruption of R8 domain function reduces load-free vinculin binding to talin, and reduces the rate of additional vinculin recruitment. Taken together, these data show that the concurrent recruitment of talin and vinculin prior to mechanical engagement with integrins is essential for the traction-mediated unfolding of talin, exposure of additional VBSs, further recruitment of vinculin, and ultimately, NA maturation.
Keywords: epithelial cells; cell adhesion; talin; vinculin; integrin; traction force microscopy